2021
DOI: 10.18203/2394-6040.ijcmph20210827
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and self-care practices of diabetic patients in an urban community

Abstract: Background: The term "diabetes mellitus" describes a metabolic disorder of multiple aetiology characterized by chronic hyperglycemia. The GOI’s NPCDCS has a focus on awareness generation for behaviour and life-style changes, screening and early diagnosis of persons with high level of risk factors and their referral to appropriate treatment facilities. Earlier studies have reported that knowledge of patients about diabetes care leads to better glycemic control.Methods: A cross-sectional study conducted over a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…For patients with higher socioeconomic status, there will be no obstacles to monitoring blood sugar regularly due to financial support. Padma et al (2012) revealed that people with Diabetes Mellitus can do self-care regularly to control their glycemic load better. while self-care according to the opinion of Orem, activities by individuals to meet the basic needs of life.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with higher socioeconomic status, there will be no obstacles to monitoring blood sugar regularly due to financial support. Padma et al (2012) revealed that people with Diabetes Mellitus can do self-care regularly to control their glycemic load better. while self-care according to the opinion of Orem, activities by individuals to meet the basic needs of life.…”
Section: Resultsmentioning
confidence: 99%